Coda. - Zurianah Hashim. (2013)
The marriage between text and image has been used often in artworks spanning across different media platforms, channelled through various techniques for a multitude of purposes. An illustration may incorporate such affiliation to present an interaction between the artist's personal expression and stylistic approach of the image, as well as presenting a semblance of narrative-in the form of words, a shared language- that encourages the audience's own interpretation of the artworks. Illustrations are being used in a variety of ways, and presented for an intent that may highlight a specific (factual or fictional) information, acting as a cornerstone for ideas to be discerned as a visual profile. This report describes the image-making process and the intricacies of storytelling, supported by the development of Coda, a compilation of digital illustrations that demonstrates the establishment of stylistic visualisation from its initial conceptuallisation to progression and production to its final stages, along with an addendum on the problems encountered during the project and the steps that were undertaken to resolve the respective complications.